Diseño de un plan estratégico para una empresa de turismo receptivo Gran Aventura S.A. ubicada al norte de la ciudad de Quito. - Días Redrobán, Andrea Elizabeth (2014)
This work is composed of four chapters which detail the different activities in the company Gran Aventura SA. The first chapter presents an introduction of the enterprise, here the problem and objectives are stated. An strategic plan is made using the most adequate tools and research methods. The second chapter explains the theoretical framework, the fundamental concepts to be applied in subsequent chapters. It also describes what strategic planning is, characteristics, importance and the benefits of it. Additional to this you will find a comprehensive content in relation to the external and internal analysis, as well as its components.